Pengaruh Formulasi Hidrokoloid Iota Karaginan Terhadap Karakteristik Kimia Dan Sensori Selai Lembaran Kacang Hijau (Phaseolus Radiatus L.) - Giovani, Sarah; Jameelah, Maryam; Putri, Afiya Deliana (Universitas Al Azhar Indonesia, 2023)
Mung bean (Phaseolus radiatus L.) sheet jam is defined as a jam product that is modified into sheet form. The characteristics of sheet jam are in the form of a compact sheet, plastic, and not sticky when removed from the packaging. Iota carrageenan is used in the manufacture of sheet jam as a texturizer to form a dense sheet texture. This study aimed to determine mung bean sheet jam's chemical and sensory characteristics. This study was experimental with a completely randomized design (CRD) with only one factor, i.e. iota carrageenan concentration (0.75%, 1.0%, and 1.25%). The results showed that the formula with the addition of iota carrageenan concentration of 1.25% (F3) was the most preferred by the panelists based on color, aroma, texture, taste, and overall parameters. The nutritional content of the mung bean sheet jam product produced from the selected formula was carbohydrate (64.97%), protein (9.44%), and fat (20.80%). The dietary fiber content of the mung bean sheet jam content product was 19.71%. Based on the Recommended Dietary Allowances (RDA) per serving (100grams) of mung bean sheet provides the energy needs of 485 kcal, 16% protein, 31% fat, and 20% carbohydrates for the general group.Keywords - Carrageenan, Jam, Mung bean, Sheet